2014
DOI: 10.1080/23335432.2014.976591
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis of the upper extremity in water polo players during water polo shots

Abstract: The purpose of this study is to understand electromyographic parameters of selected shoulder and arm muscles in water polo shots. The study was carried out with a group of 12 water polo players. Signals were recorded by surface electromyography (EMG) from the pectoralis major (PM), anterior deltoid (AD) and middle deltoid (MD), biceps brachii (BB), triceps brachii (TB), and wrist flexor (WF) muscles. The average and standard deviation of the normalized electrical activity and duration of the muscles were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…According to [22], on the side of the more general performance characteristics of the players' the age [17] and body height [21] are primary variables that influence the throwing velocity. On the side of the trainable physical components, hand grip strength [36] as well as shoulder rotator strength [18,37], specifically the pectoralis major muscle and deltoid muscle strength [38], and in-water shoulder proprioception [39], are the main determinants of throwing speed. Also a positive impact on throw velocity was shown for the vertical jump height by means of the water polo boost, and the height of the head above the water surface during the throw [17].…”
Section: Biomechanical Analysis Of the Goal Shot Behavior Of Individual Playersmentioning
confidence: 99%
“…According to [22], on the side of the more general performance characteristics of the players' the age [17] and body height [21] are primary variables that influence the throwing velocity. On the side of the trainable physical components, hand grip strength [36] as well as shoulder rotator strength [18,37], specifically the pectoralis major muscle and deltoid muscle strength [38], and in-water shoulder proprioception [39], are the main determinants of throwing speed. Also a positive impact on throw velocity was shown for the vertical jump height by means of the water polo boost, and the height of the head above the water surface during the throw [17].…”
Section: Biomechanical Analysis Of the Goal Shot Behavior Of Individual Playersmentioning
confidence: 99%
“…Furthermore, water polo requires ball throwing, repetitive passing, and shooting, which involve shoulder abduction and maximal external rotation (ER) at high speed ( Melchiorri et al, 2011 ). In most water-based launches, there is a greater demand on the musculature of the shoulder ( Yaghoubi et al, 2014 ), increasing the load and risk of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified the scapular stabilizers (supraspinatus, infraspinatus, subscapularis, and middle trapezius) and internal rotators (latissimus dorsi and pectoralis major) as important contributors to the freestyle stroke (Nuber et al, 1986 ; Pink et al, 1991 ; Weldon and Richardson, 2001 ; Bedi, 2011 ). For water polo, the posterior deltoid, supraspinatus, and middle trapezius muscles play active roles in the cocking phase of the throwing task, and the pectoralis major and anterior deltoid in the follow through (Fleisig et al, 2009 ; Weber et al, 2014 ; Yaghoubi et al, 2014 ). When throwing while in water, the lack of a base of support requires the shoulder joint to produce more force than overhead throwing performed on land (Feltner and Taylor, 1997 ).…”
Section: Introductionmentioning
confidence: 99%